Effects of insecticidal proteins of Enterobacter cloacae NK on cellular immunity of Galleria mellonella larvae - Liao, Chunli; Huang, Ran; Yang, Yi; Huang, Yapeng; Zhang, Kai; Ma, Liang; Li, Taotao; Wang, Lianzhe; Zhang, Huamin; Li, Bingbing (Frontiers in Microbiology, 2023)
Enterobacter cloacae produces insecticidal proteins capable of causing toxicity in pests, but the insecticidal mechanisms of these proteins for insect control remain unclear. To elucidate the mechanisms, the purified insecticidal protein from E. cloacae NK was administered to Galleria mellonella larvae either by intraperitoneal injection or by feeding. The number of hemocytes, apoptosis in immune cells, and polyphenol oxidase (PO) activity of G. mellonella larvae were detected by hemocytometer, Annexin V-FITC/PI, and UV–vis spectrophotometer, respectively. With the extension of the invasion time of NK insecticidal protein, the number of hemocytes in G. mellonella larvae decreased significantly (p < 0.05), whereas the apoptosis rate of hemocytes increased. The activity of PO showed a trend of rising-peak-sharp decline and the melanization reaction was deepened simultaneously. Moreover, the phagocytosis and coating capabilities of hemocytes decreased, and the intraperitoneal injection method was more effective than the feeding method. Taking together, the insecticidal protein of E. cloacae NK inhibits and destroys the cellular immune response of G. mellonella larvae, which suggests an important role in killing the host insect.